We have the ability to serenely aggregate, account and reap - Mizusaki, Jorge Mitsuo (Scientific Journal of the Foot & Ankle, 2019)
We are going through a political, economic and social moment when human relations are fragmented. There is an attempt to impose wills that dominate economic power over disadvantaged people, as regularly shown. The leaders of the most powerful nations try to subdue those without economic assets, blocking people's free movement through land and sea blockages, and strengthening land confinements. While others always wait for some heroic attitude. In our activity as orthopaedic doctors, surgeons or managers we also face strong economic and financial impositions, "windows close but doors open." The speed of information in the current times will determine in the near future the quality of services that will be required, both for the ethical characterization of the information and for its credibility. Not long ago, the main complaint of ABTPé members was related to professional remuneration. We observed that the purposeful attitude of all associate members and the willingness of some members led to the beginning of change. We begin to consider the ethical views of payer and service provider, the legal aspects of adoptable attitudes, as well as the ethical attitudes of medical practice. Thus, these facts illustrate the strength and ability of fellow foot and ankle surgeons to take action that results in advantages for the entire class. These facts illustrate the strength and ability of foot and ankle surgeons to take action that results in advantages for the entire ABTPé. Making an analogy with the field of scientific culture we must also show how capable we are in producing useful scientific knowledge that benefits everyone. Creativity will be present with the release of new space for presentation of innovative procedures, through the technical notes in our publications. Discussions should be stimulated. The willingness of foot and ankle surgeon training centers to cultivate purposeful, ethical and socially comprehensive attitudes becomes extremely relevant. Thus, we will keep the flow of scientific development, improving our publications and projecting the potential of generating new knowledge compatible with our socioeconomic and cultural conditions. Our strength in producing publications capable of summing up the various currents of thought and our cultures will set our continent on a new level. In this edition we are considering the internationalization of knowledge. Yes, we are capable. Everyone's effort will be worth the award. Have a great reading. Jorge Mitsuo Mizusaki Editor-in-Chief